Fleabag the special edition - Waller-Bridge, Phoebe 1985- (Nick Hern Books, 2019)
Celebrate the incredible journey of Phoebe Waller-Bridge's outrageously funny, blazingly forthright Fleabag, from fringe theatre hit to international cultural phenomenon, in this special edition - featuring the original playscript, never-before-seen colour photos, and exclusive bonus content by Phoebe, director Vicky Jones and key members of the creative team.In 2013, Fleabag made its debut as a one-woman show in sixty-seater venue the Big Belly, at the Edinburgh Festival Fringe's Underbelly. It was an immediate hit, going on to enjoy two runs at London's Soho Theatre, national and international tours, whilst picking up prizes including Critics' Circle, The Stage, Fringe First and two Off West End Theatre Awards, plus an Olivier Award nomination.The 2016 TV adaptation propelled Fleabag and Phoebe to worldwide fame, earning critical acclaim and further accolades including Writers' Guild, Royal Television Society and BAFTA Television Awards. A second series followed in 2019, winning an amazing six Emmy Awards (including Outstanding Comedy Series and Outstanding Writing for a Comedy Series), along with a sold-out run of the original play in New York.This special edition of the play is released alongside Fleabag's first West End run at Wyndham's Theatre, London. It is introduced by Deborah Frances-White, stand-up comedian, writer and host of The Guilty Feminist podcast